“You walk on glass if you are in that space”: Risks and harms of corruption in wildlife justice pathways in Uganda - Anne-Marie Weeden; Nicholas Pamment (Journal of Economic Criminology)
Wildlife crime drives existential harms including biodiversity loss and climate change, disproportionately affecting the Global South. Criminal justice approaches dominate the public response, yet scant evidence exists on how corruption, an economic crime, undermines deterrence and exacerbates inequalities. This primary research study utilises a qualitative approach to examine the risks and harms of corruption within wildlife enforcement and justice in Uganda. Using a red-green criminological perspective and drawing upon semi-structured interviews with experts and practitioners from government and civil society, this paper identifies corruption risks in wildlife criminal justice and explores their related harms and consequences. The study finds wildlife enforcement in Uganda suffers from institutional corruption, including perverse incentives which distort targeting and resource prioritisation, leading to discrimination against low-level offenders. Furthermore, differential access to individualist corruption opportunities along the justice pathway enables wealthy or well-connected suspects to avoid sanctions, resulting in sentencing inequities. Despite resulting in differential outcomes for affluent and subsistence offenders, the study concludes that corruption in wildlife justice neutralises deterrence for both offender types. By creating impunity for elites, organised crime actors are attracted to the trade. Moreover, by amplifying sentencing inequalities, subsistence offenders are further impoverished, increasing re-offending. Corruption in wildlife justice thus drives significant long-term environmental, socioeconomic, and political harms, and erodes the rule of law.